Sex-specific prediction equations for Vmax(FRC) in infancy: a multicenter collaborative study - Hoo, Ah-Fong; Dezateux, Carol; Hanrahan, John P; Cole, Tim J; Tepper, Robert S; Stocks, Janet (American journal of respiratory and critical care medicine, 2002)
Measurements of maximal flow at functional residual capacity (Vmax(FRC)) from partial forced expiratory maneuvers remain the most popular method for assessing small airway function in infants and young children. However, the lack of appropriate reference data that are both applicable outside the centers that developed them and reflect the normal variability between healthy subjects has limited interpretation of Vmax(FRC) results in both clinical practice and research. To address this problem, we collated Vmax(FRC) data from 459 healthy infants (226 boys) tested on 654 occasions during the first 20 months of life from three collaborating centers. Multiple linear regression analysis indicated that sex, age, and length were important predictors of Vmax (FRC), which was, on average, 20% higher in girls than in boys during the first 9 months of life. (Vmax(FRC))0.5 (ml x second(-1)) = 4.22 + 0.00210 x length2 (cm) for boys (RSD = 3.01; R2 = 0.48), and -1.23 + 0.242 x length for girls (RSD = 2.72; R2 = 0.49). Alternative models incorporating both age and length z scores are also described. Failure to use sex-specific prediction equations for Vmax(FRC) may preclude detection of clinically significant changes in girls and lead to false reports of diminished airway function in boys. Appropriate use of z scores, which indicate a "normal" range (z scores of 0 +/- 2) for Vmax(FRC), during infancy should also improve interpretation of both clinical and research studies.